Work on the pronunciation of vowels and consonants in elementary grades - Ahunjanov Ibragim (Zien Journals, 2022)
Language learning at school from the very first steps is characterized by an inextricable link between the child's speech development and mastering the basic knowledge about the structure of the language, its basic units, which creates the necessary basis for the conscious improvement of speech, both oral and written.
Keywords: language teaching; education; methodological systems; exercises